Podcast Sebagai Peluang Radio Elshinta Menambah Pendengar Dan Pendapatan - Haryo Ristamaji; Pitoyo Pitoyo (Institut Nalanda, 2024)
Radio Elshinta is a national private radio station in Jakarta that carries the tagline